Impact of hearing loss in the lives of geriatric individuals - Jain, Archita; Thomas, James (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Hearing loss in old age is a vexing problem and millions of people worldwide are suffering from it. The aim of this study is to identify the problems which geriatric individuals with hearing loss experience and to help them to overcome their disability and its effects on social engagement and interpersonal relationship. Methods: The study was conducted in a tertiary care hospital and is based on prospective study. The data collection was done in the form of confrontational interview. Results: According to our study individuals suffering from moderate hearing loss have difficulty in communicating with friends, relatives and even strangers. They even face problems in travelling. They feel disoriented during conversation and tend to miss out parts of conversation. They tend to use their visual signals more than hearing for example while watching television they try to focus and interpret more by the video than by listening to the audio. People suffering from mild to moderate hearing loss try to ignore the disability and request people to repeat statements but inadvertently still miss out the conversation and the try to ignore the handicap. Conclusions: Age related hearing loss known as presbycusis and it is one of the most prevalent conditions in old age and millions of people worldwide are afflicted. It is one of the leading cause of overall diminution of physical and mental performance in old age. It is often neglected and remains undetected for long in geriatric population due to gradual progression.